Spatial-Temporal Analysis of Deforestation in Sumatera Island 2011-2019 - Andrian Dwi Putra; Siskarossa Ika Oktora (Politeknik Statistika STIS, 2021)
The existence of forests is threatened with deforestation, which can affect climate disturbances and environmental decay. This study aims to analyze determinants of deforestation in Sumatera Island from 2011-2019. The dependent variable is deforestation, and the independent variables are population density, land fires, road length, GDP of agricultural, fisheries, and forestry, and GDP of mining and excavation. The results show that there is spatial-temporal heterogeneity in deforestation in Sumatera Island from 2011-2019. Furthermore, because of the normality violation, the Robust Geographically and Temporally Weighted Regression (RGTWR) method is used. Analysis shows variables affecting deforestation in Sumatera Island vary in each province and change annually. Land fires were always significant in every province and every year from 2011-2019. To overcome deforestation, the governments need to consider the varying causes of deforestation, more firmly to forestry regulation and establish cooperation with local communities in managing forest.